2019
DOI: 10.1016/j.euroecorev.2019.103313
|View full text |Cite
|
Sign up to set email alerts
|

A war is forever: The long-run effects of early exposure to World War II on trust

Abstract: This paper examines the long-term effect of conflict on trust by using changes in places and timing of combats during World War II. We focus on the pre-school period, an important life stage for the formation of trust and an age where war exposure may persist throughout life. We find robust evidence that individuals exposed to combats in the first six years of life display lower trust and social engagement well into adulthood. In light of the well-known relationship between trust and collective action, our res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 80 publications
(85 reference statements)
3
16
0
Order By: Relevance
“…We find that parental separation is associated with lower trust (but not risk aversion) in adolescence and early adulthood. The reduction in trust is strongest when parental separation occurs between the ages of 0-6, which supports arguments that this is a critical period for the formation of trust, where disruptive events might be particularly influential (Conzo and Salustri, 2019).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…We find that parental separation is associated with lower trust (but not risk aversion) in adolescence and early adulthood. The reduction in trust is strongest when parental separation occurs between the ages of 0-6, which supports arguments that this is a critical period for the formation of trust, where disruptive events might be particularly influential (Conzo and Salustri, 2019).…”
Section: Discussionsupporting
confidence: 74%
“…to 17) has no negative bearing. These results complement the findings of Conzo and Salustri (2019). For risk, the pattern appears to be reversed, with only the later years (ages 12 to 14) revealing a potential consistent reduction in children's willingness to take risks-however, the volatile estimates and absence of any average e↵ects do not let us draw any firm conclusions.…”
Section: Results By Age At Separationsupporting
confidence: 67%
See 1 more Smart Citation
“…Consider that the fraction of migrants in our sample, though it may seem too low (2%), is in line with external data: the population in our sample countries was about 344 million in 1939 15 , while the estimated number of refugees in Europe in 1945 was around seven million (Barnett, 2002). Regarding out-of-sample migration, Kesternich et al (2014) and Conzo and Salustri (2017) provide evidence that migration outside the countries in our sample during and after the war (1939)(1940)(1941)(1942)(1943)(1944)(1945)(1946)(1947) was not easy. In addition, migration to the US from the 1920s to 1965 was at its minimum levels due to restrictions, imposing a ceiling on the number of immigrants accepted each year.…”
Section: Robustness Checkssupporting
confidence: 79%
“…Early-life exposure to conflict shapes human capital outcomes in later life, and also affects social preferences in a persistent way: Conzo and Salustri (2017) and Grosjean (2014) found that WW2 made exposed individuals less trusting. Hörl, Kesternich, Smith, and Winter (2016) found hunger episodes in German cohorts born after WW2 to have a similar effect on trust.…”
Section: Major Early Life Experiences and Adulthood Outcomesmentioning
confidence: 99%